ANALISIS KESENJANGAN PROSES BISNIS DENGAN BLUEPRINT IMPLEMENTASI SISTEM ENTERPRISE RESOURCE PLANNING (ERP) - Bagaskara, Wahyu Fahmi; Anggraeni, Rila (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Mendekorumah is a small medium enterprise, engaged in furniture and interior design, and production by make to order. The problems process of distribution information SME’s with business activities conducted manually. An information system can help the industry SME’s in improving the effectiveness of the activities of companies is the enterprise resource planning. The research purposes is to be able to implement ERP for SME’s Mendekorumah so that the problems faced can be resolved. The type of research used is descriptive qualitative method, data analysis methods data obtained from interviews, field notes and documents. In the results, in Mendekorumah it was found that automatic records such as business partner master data, product master data recording, running business processes.Mendekorumah has not implemented the ERP system, the blueprint used to find out changes in business processes later when implemented next step. The gaps found in business processes between the ERP implementation blueprint and current business processes Mendekorumah updated business processes by implementing an ERP system for recording all activities and further modernizing business processes.